iTRAQ Proteomic Analysis of Continuously Cropped Soybean Root Inoculated With Funneliformis mosseae - Bai, Li; Sun, Hai-Bing; Liang, Rui-Ting; Cai, Bai-Yan (Frontiers in Microbiology, 2019)
Soybean (Glycine max) is susceptible to root rot when subjected to continuous cropping, and this disease can seriously diminish the crop yield. Proteomics analyses can show the difference of protein expression in different treatment samples. Herein, isobaric tag for relative and absolute quantitation (iTRAQ) labeling and liquid chromatography-tandem mass spectrometry (LC-MS/MS) were employed for proteomic analysis of continuously cropped soybean inoculated with the arbuscular mycorrhizal fungus (AMF) Funneliformis mosseae. The AMF can reduce the incidence of root rot and increase plant height, biomass index in 1, 2 and 4 year of continuous cropping. Differential expression of proteins in soybean roots was determined following 1 year of continuous cropping. A total of 131 differentially expressed proteins (DEPs) were identified in F. mosseae-treated samples, of which 49 and 82 were up- and down-regulated, respectively. The DEPs were annotated with 117 Gene Ontology (GO) terms, with 48 involved in biological processes, 31 linked to molecular functions, and 39 associated with cell components. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis mapped the DEPs to 113 mainly metabolic pathways including oxidative phosphorylation, glycolysis and amino acid metabolism. Expression of glucan 1,3-beta-glucosidase, chalcone isomerase, calcium-dependent phospholipid binding and other defense-related proteins was up-regulated by F. mosseae, suggesting inoculation promotes the growth and development of soybean and increases disease resistance. The findings provide an experimental basis for further research on the molecular mechanisms of AMF in resolving problems associated with continuous soybean cropping.